دلالة الرمز الصوفي للمرأة والخمر في شعر عبدالغني النابلسي ت. 1147 هـ. - صحصاح، محمد أحمد عبدالفتاح (جامعة الأزهر - كلية اللغة العربية بإيتاي البارود, 2022)
يمثل الشعر الصوفي جزءًا من التراث الأدبي، ولونًا من ألوان الأدب عبر العصور المختلفة، والتصوف في عصر النابلسي (العصر العثماني) كان امتدادًا للتصوف الذي عرف أواخر عصر المماليك، وإن اختلفت تياراته في العصرين قوة وضعفًا، ولما كان (النابلسي) أبرز شعراء التصوف في عصره، جاءت هذه الدراسة تتغيا الكشف عن دلالة الرمز الصوفي للمرأة والخمر في شعره، حيث مثلت المرأة رمزًا مهمًا، إن لم يكن أهم رمز في الشعر الصوفي على الإطلاق، ذلك أن المرأة في الغزل الصوفي والحب الإلهي هي رمز الذات الإلهية، وقضية الحب الإلهي هي محور الشعر الصوفي، وكما استخدم الشاعر لغة الغزل في التعبير عن مواجيده، وأسراره العرفانية استخدم كذلك الخمر فاستلهم التراث الهائل من الشعر الخمري، وصاغه بحيث يتلاءم مع ما يتعاطى من أحوال وأسرار، والخمر في شعر الصوفية ليست هدفًا في حد ذاتها، وإنما هي سبيل التجلي الشعري للمخبوء في لونها وصفاتها وفعلها، وقد كان من أسباب اختيار هذا الموضوع: أن رمزي المرأة والخمر هما الأكثر انتشارًا في ديوان النابلسي، وعدم وجود دراسة مستقلة- في حدود ما أعلم- تتناول الرمز الصوفي عند النابلسي، والمنهج المتبع في هذه الدراسة هو المنهج التحليلي الوصفي، الذي يتتبع الظواهر من خلال المادة الشعرية، ويحللها ويقسمها إلى رؤى، وأفكار وموضوعات. Sufi poetry is part of the literary heritage, and a color of literature through different ages. Sufism in the Nabulsi era (the Ottoman era) was an extension of the mysticism that was known at the end of the Mamluk era, although its currents differed in strength and weakness in the two eras. Where the woman represented an important symbol, if not the most important symbol in Sufi poetry at all, because the woman in the mystical spinning and divine love is the symbol of the divine self, and the issue of divine love is the focus of mystical poetry, and as the poet used the language of spinning to express his glory, and his mystical secrets He also used wine, so he drew inspiration from the vast heritage of Khmer poetry, and formulated it in a manner that suits the conditions and secrets he deals with, and wine in Sufi poetry is not a goal in itself, but rather is the way of poetic manifestation of what is hidden in its color, qualities and action, and one of the reasons for choosing this topic was: that The symbols of women and wine are the most prevalent in Nabulsi’s Diwan, and there is no independent study - as far as I know - dealing with the mystical symbol of Nabulsi, and the approach followed in this study is the descriptive analytical method, which traces phenomena through poetic material, And analyzes and divides them into visions, ideas and topics.
Keywords: الشعر الصوفي -- الرموز الشعرية -- النابلسي، عبدالغني، ت. 1147 هـ